Assessing Mand Topography Preference When Developing a Functional Communication Training Intervention. Issue 3 (May 2018) - Kunnavatana, S. Shanun; Wolfe, Katie; Aguilar, Alexandra N.
Functional communication training (FCT) is a common function-based behavioral intervention used to decrease problem behavior by teaching an alternative communication response. Therapists often arbitrarily select the topography of the alternative response, which may influence long-term effectiveness of the intervention. Assessing individual mand topography preference may increase treatment effectiveness and promote self-determination in the development of interventions. This study sought to reduce arbitrary selection of FCT mand topography by determining preference during response training and acquisition for two adults with autism who had no functional communication skills. Both participants demonstrated a clear preference for one mand topography during choice probes, and the preferred topography was then reinforced during FCT to reduce problem behavior and increase independent communication. The implications of the results for future research on mand selection during FCT are discussed.